Disease Pattern among the Patients of Sexually Transmitted Infection : A Cross Sectional Study of 70 Cases - Ahmed, Shalahuddin (IAHS Medical Journal, 2024)
Background: Sexually Transmitted Infections (STIs) including Human Immunodeficiency Virus (HIV) continue to present major health problems in Bangladesh, leading to considerable morbidity, mortality and stigma. To determine the diseases pattern among the patients of sexually transmitted infection attending at the Department of Dermatology and Venereology, Bangabandhu Memorial Hospital of Chattogram, this study was performed. Materials and methods : This cross sectional study was carried in the Department of Dermatology & Venereology, Bangabandhu Memorial Hospital, Chattogram during the period August to November 2023. A total of 70 cases were enrolled in this study. Among them, 58 patients were male and 12 patients were female. Results: Genital ulcer (28.57%) was the most common clinical presentation among the attendees. Primary syphilis was the most common (18.57%) STI detected among the participants followed by herpes genitalis (17.14%). The most common mixed infection was primary syphilis with chancroid (33.34%) followed by herpes genitalis with primary syphilis (25%). Conclusion: Ulcerative STIs singly or in combination are more frequent than the non-ulcerative STIs. IAHS Medical Journal Volume 06(2), December 2023; 5-8